MAKNA SIMBOLIS LAKON KANGSA ADU JAGO DALAM PERTUNJUKAN WAYANG KULIT PURWA - -, Randiyo (Harmonia: Journal of Arts Research and Education, 2011)
Lakon Kangsa Adu Jago merupakan salah satu lakon carangan yang bermutu yang mengandung nilai dan bermakna simbolis. Adu Jago mewakili suatu tindakan simbolis karakter generasi tua melawan generasi muda. Disebabkan oleh simbolis yang kurang adil, bijaksana, terjadilah keteledoran penguasa Mandura yaitu Basudewa. Di balik peristiwa adu jago sebenarnya Kangsa ingin merebut kekuasaan dari tangan Basudewa. Yang dapat dipetik dari lakon ini adalah munculnya tokoh Pandawa, simbol kesatria pembela keadilan, penuh pengabdian yang berhasil membantu menyelasaikan kewajibannya. Melalui lakon Kangsa Adu Jago, semangat persatuan, keadilan, kebenaran menjadi lebih kuat, terbentuklah kesatuan nasib antara keluarga Yadawa dengan Barata. Simbol karakter tokoh dalam lakon memunculkan nilai herois dan pendidikan untuk dijadikan contoh teladan dalam hidup manusia. Symbolic Meaning of Kangsa Adu Jago (Cock Fighting) Play in Purwa Shadow Leather Puppet Show Abstract Kangsa Cock Fighting Play is a qualifi ed carangan play containing certain symbolic meaning. Adu Jago (Cock Fighting) represents a symbolic action of old generation character against young generation one. Behind the cock fi ghting, Kangsa actually desired to seize power out of Basudewa’s hand. This play especially reveals certain values through the fi gure of Pandawa, a knightly character who strove for justice and with his great dedication succeeded in carrying out his duties. The values conveyed by this Kangsa Cock Fighting play are hopefully expected to be able to build up a stronger spirit of unity, justice, and truth by especially learning from the destiny unity between Yadawa and Barata families. The symbolic characters in the play accordingly reveal heroic and educative qualities as examples for human’s lives. Keywords: adu jago, lakon, wayang kulit purwa, kangsa